(untitled) (Al-Academy, 2021)
The issue of the other in the graphic design and specifically the advertising constitutes a cognitive study of the structure of the intellectual expansion in the cognitive and intellectual creative systems because of the implicit and declared embodiment it provides within the mechanisms of reading in the advertising design that appeared according to the other and through the embodiment of the textualism, the difference and the binary opposites is nothing but a reaction to the design thought and what constitutes of the manifestations of the other in advertising design. Based on the above, we review this study (Manifestations of the Other in Graphic Design) to clarify the topic through four chapters. The first chapter included the research problem by asking the following question (What are the manifestations of the other in graphic design) As for the aim of the study (to identify the manifestations of the other in graphic design) and also included the importance of research which will contribute to a scientific step in understanding the phenomenon of the manifestations of the other, which entered through various intellectual and literary trends within the text and their harmony with the artistic trends bordering with them and may benefit specialists in the field of advertising design by crystallizing the thinking of the graphic designer to achieve design intellectual creativity. As well as defining terms. As for the second chapter, it included (the concept of the other) and (the mechanisms of reading the advertising design according to the other) and the third chapter reviewed the conclusions that included:1- The other is represented by its movement as a new artistic system, through its connection with the concepts of transformation, development and change, being the concepts of implicit mechanisms in the manifestation of the other in the advertising through its transition from the fixed to the transformed to reach new forms that do not last until they are subject to the other towards constructive transformations.2- All the ideas that try to revive the other were represented in forming a structure of equivalents linked by mediating relationships for the re-creation through continuous transformation, or through complementary and enriching relationships between references.3- The multiplicity of the manifestations of the other through the mechanisms of reading the advertising design to build it at the level of forming a design structure, or thought, which is done by one or more of the secondary indicators; textualism, difference and binary opposites.In light of the conclusions reached by the study, the researcher recommended the following:1- The possibility of investing the other in graphic design through propositions that clarified the manifestations of the other in advertising design by altering and displacing previous patterns and generating different and new shapes.2- The study recommends making use of theoretical thought and investing it and relying on methods and procedures that the other proposes about the past, and to generate various new forms and meanings in advertising design.